2014
DOI: 10.1021/cs500138j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Li Doping on MgO-Supported Sm2O3 and TbOx Catalysts in the Oxidative Coupling of Methane

Abstract: Rare earth oxides (REOs), particularly the sesquioxides, such as Sm 2 O 3 and La 2 O 3 , have been investigated as promising catalysts in the oxidative coupling of methane (OCM). Much less attention has been paid to the reducible REOs because they are expected to give oxidation products, such as CO and CO 2 (CO x ), rather than the desirable ethane and ethylene (C 2+ ). Because Li addition can improve the performance of Sm 2 O 3 in the OCM reaction and Li/MgO is commonly used as a reference OCM catalyst, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 48 publications
0
20
1
1
Order By: Relevance
“…Compared to the SiO 2 -supported catalysts, the surface area of the Mn-Na 2 WO 4 /n-MgO is higher. In fact, the surface area of the n-MgOsupported Mn-Na 2 WO 4 catalyst (12.3 m 2 /g) is higher than our previously reported Li-TbO x /nMgO catalyst (5.6 m 2 /g) [29]. While a high surface area normally is a desirable property of heterogeneous catalysts, this is not necessarily true in OCM, since a high surface area can induce unwanted side reactions on the surface, with a concomitant reduction in selectivity.…”
Section: Bet Surface Area Measurementscontrasting
confidence: 67%
“…Compared to the SiO 2 -supported catalysts, the surface area of the Mn-Na 2 WO 4 /n-MgO is higher. In fact, the surface area of the n-MgOsupported Mn-Na 2 WO 4 catalyst (12.3 m 2 /g) is higher than our previously reported Li-TbO x /nMgO catalyst (5.6 m 2 /g) [29]. While a high surface area normally is a desirable property of heterogeneous catalysts, this is not necessarily true in OCM, since a high surface area can induce unwanted side reactions on the surface, with a concomitant reduction in selectivity.…”
Section: Bet Surface Area Measurementscontrasting
confidence: 67%
“…While Mn-Na 2 WO 4 /SiO 2 is considered to be the state-of-the-art OCM catalyst, it is a very complex system, and the nature of the active sites is still under debate [7]. Li/MgO is receiving less attention in recent literature as it is associated with rapid deactivation due to Li removal during reaction [8,9]. Other catalysts commonly used for the OCM reaction are doped and undoped rare earth oxides (REOs) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al used high-k Sm 2 O 3 thin film as a pH-sensing layer [5]. Application to catalyst has also been of interest [6][7][8][9][10]. Elkins et al demonstrated that Sm 2 O 3 could be a promising catalyst for the oxidative coupling of methane [8].…”
Section: Introductionmentioning
confidence: 99%
“…Application to catalyst has also been of interest [6][7][8][9][10]. Elkins et al demonstrated that Sm 2 O 3 could be a promising catalyst for the oxidative coupling of methane [8]. Wang et al reported a potential application to photocatalytic dye degradation [9,10].…”
Section: Introductionmentioning
confidence: 99%